Assessing Adverse Childhood Experiences during Pregnancy: Evidence toward a Best Practice - Megan W. Nguyen; Emily Heberlein; Sarah Covington-Kolb; Anne M. Gerstner; Amber Gaspard; Kacey Y. Eichelberger (Thieme Medical Publishers, Inc., 2019)
Abstract Objective To quantify the prevalence of adverse childhood experiences (ACEs) among a diverse urban cohort of pregnant women. Study Design The ACE survey was self-administered to 600 women categorized evenly between the waiting room, private examination rooms, and CenteringPregnancy group spaces. The percentage of women willing to complete the survey per location was compared using chi-square tests, and the mean ACE score per arm was compared using Wilcoxon's rank-sum test. Results Of the 660 women approached for participation, 5% declined; 67% reported ≥ 1 ACE exposure and 19% reported an ACE score of ≥ 4. By domain, 59% experienced household dysfunction, 25% abuse, and 25% neglect. Women in the waiting room were more likely to decline participation (p < 0.01), and those participating in the postpartum inpatient arm had a significantly lower proportion affirming 8 of 10 ACE questions, were less likely to report ≥1 ACE, and had a lower mean ACE score when compared with the outpatient arm (p < 0.01). Conclusion The prevalence of ACEs in this diverse pregnant cohort was high. The ideal locations to distribute the survey are the outpatient examination rooms.